USERS' SOCIOCULTURAL ORIENTATION AND SMART SYSTEMS ACCEPTANCE LINK: DO DEMOGRAPHICS MATTER?. Issue 3 (3rd July 2019) - Talukder, Majharul; Alyammahi, Sultan; Quazi, Ali; Abdullah, Abm; Johns, Raechel
ABSTRACT: This research investigates the impact of sociocultural determinants on people's perceptions and usage of smart systems in the United Arab Emirates (UAE). This research used the Theory of reasoned action, Unified theory of acceptance and use of technology (UTAUT) and Frambach and Schillewaert's framework. These theories which focus on the determinants of technology acceptance behavior of users have been widely used in contemporary technology acceptance research. Data were collected from the UAE Ministries of Foreign Affairs, Health, and Economy using structured questionnaires. A total of 357 responses were analyzed using multivariate statistical techniques such as regression analysis and factor analysis. Multiple regression analysis helped to determine the direction of relationships between the constructs representing users' sociocultural orientation, attitude toward smart systems and acceptable behavior. Factor analysis served to identify the underlying dimensions of the above constructs. The major finding of this research is that cultural values and peers' influence significantly affect users' perceptions and applications of technological innovations. Furthermore, the study reveals that users' age and gender wield critical moderating effects on the relationship between cultural values and attitude toward smart systems. These findings have important implications for acceptance and implementation of smart systems in the UAE which are highlighted in this paper. This paper also identifies the limits of this research and explores the venues of further research in this field.